Recurrence after endoscopic piecemeal mucosal resection for large sessile colorectal polyps - Seo, Guh Jung (The WJG Press and Baishideng, 2010)
AIM: To evaluate the safety and outcomes of endoscopic piecemeal mucosal resection (EPMR) for large sessile colorectal polyps. METHODS: The patients enrolled in this study were 47 patients with 50 large sessile polyps (diameter, 2 cm or greater) who underwent EPMR using a submucosal saline injection technique between December 2002 and October 2005. All medical records, including characteristics of the patients and polyps, complications, and recurrences, were retrospectively reviewed. The first follow-up endoscopic examination was performed at 3-6 mo after initial endoscopic resection, and the second at 12 mo post-EPMR. Subsequent surveillance colonoscopic examinations were individualized, taking risk factors into account. RESULTS: The patients were 23 men and 24 women, with a mean age of 60 years. Mean polyp size was 30.1 mm. Of 50 polyps identified, 34 (68%) were benign and 16 (32%) were malignant. There were 6 (12%) cases with EPMR-related bleeding: 5 intra-procedural and 1 early post-procedural bleeding. All bleeding episodes were managed by endoscopic clipping or argon beam coagulation. There were no perforations. Recurrence was identified in 5 cases (12.2%): 4 local recurrences detected at 3 mo post-EPMR and 1 local recurrence detected at 14 mo post-EPMR. The recurrence rate after EPMR was 3.1% for benign polyps and 33.3% for malignant polyps (P < 0.05). Median follow-up time was 37 mo. CONCLUSION: EPMR is safe, but should be applied carefully in malignant polyps. Close follow-up endoscopic examinations are necessary for early detection of recurrence.